The Relationship of Fast Food Consumption, Nutritional Status, and Sedentary Lifestyle with Adolescent Hypertension - Henika Ardelia; Hidayatusy Syukrina Puteri; Asep Jalaludin Saleh (CV. CENDIKIA JENIUS INDONESIA, 2025)
Hypertension, once predominantly found in adults, is increasingly prevalent among adolescents, primarily due to unhealthy eating habits, imbalanced nutritional status, and a sedentary lifestyle. This condition is concerning because early-onset hypertension raises the risk of cardiovascular disease later in life. This study aimed to determine the relationship between fast food consumption, nutritional status, and sedentary lifestyle with the incidence of hypertension among adolescents at SMAN 1 Sukoharjo. A quantitative approach with a cross-sectional design was used. The sample consisted of 93 students selected through simple random sampling. Data were collected during May–June 2025 using the Food Frequency Questionnaire (FFQ), Adolescent Sedentary Activity Questionnaire (ASAQ), blood pressure measurements, and body mass index-for-age (BMI/A) calculations. Data analysis was conducted using the Spearman Rank correlation test. The results showed no significant relationship between fast food consumption (p=0.799), nutritional status (p=0.259), or sedentary lifestyle (p=0.739) and the incidence of hypertension. Conclusion: None of the three variables had a significant effect on adolescent hypertension in the study location. Recommended health education regarding balanced nutrition and active lifestyles remains essential as a preventive measure to reduce the risk of hypertension from an early age.